Differential responses of litter decomposition to regional excessive nitrogen input and global warming between two mangrove species. (15th December 2018) - Yang, Ziyao; Song, Weimin; Zhao, Yan; Zhou, Jian; Wang, Zhonglei; Luo, Yiqi; Li, Yuhong; Lin, Guanghui
Abstract: Excessive nitrogen (N) input and warming affect litter decomposition and nutrient dynamics, especially in coastal areas. Understanding how mangrove litter decomposition responds to both excessive N input and warming is essential for estimating coastal carbon (C) and N cycling in the context of global change. In this study, we measured litter quality before and during the decomposition process of two mangrove species— Avicennia marina, a pioneer species, and Bruguiera gymnorrhiza, a late successional species—in a controlled experiment under treatments of N addition and warming. These two species dominate mangroves in southern China. Mass loss, C and N contents, and isotope values were measured over time as litter decomposed. N addition significantly increased the dry mass loss rates of B. gymnorrhiza litter by 52%, and warming significantly enhanced the dry mass loss of both A. marina and B. gymnorrhiza litter by 43% and 112%, respectively. N loss rate was not affected by the treatments but differed between the two mangrove species. There were no discernible changes in litter δ 13 C or δ 15 N throughout the decomposition process under N addition or warming, but the litter δ 15 N content was higher for A. marina than for B. gymnorrhiza, which indicated feedback between decomposers and litter chemistry. These results highlight that the litter decomposition rates of both mangrove species respond positively to regional N loading or global warming. The litter decomposition rate differed significantly between mangrove species because of differences in litter N content, C/N ratio and associated microorganisms. Highlights: Mangrove litter decomposition respond positively to nitrogen addition and warming. Litter decomposition rate differed significantly between mangrove species. Isotopic fractionation during decomposition lead to the δ 13 C enrichment of mangrove litters in the late stage.